The Water, Pine and Stone Retreat Collection : Contemporary Chinese Paintings. (Vancouver : Vancouver Art Gallery, 1987)
Chen Chikwan ; Fang Zhaoling ; Fu Baoshi ; Gao Jianfu ; Ho Huai-shuo ; Li Hua ; Li Yihong ; Lin Fengmian ; Liu Kuo-sung ; etc.
The Water, Pine and Stone Retreat Collection : Contemporary Chinese Paintings, Vancouver Art Gallery, Vancouver, June 19 - August 9, 1987
English
kunstcatalogus
Keywords: China